Influence of Tonifying Selected Body Meridians by Low Level Laser and Phonophoresis on Mechanical Neck Pain - Mohamed, Ahmed Mahmoud; Hassan Mohamed Sliman, Ashraf; Hussein, Noha Gohdan; Morsy, Mona Ebrahim (Journal of Neonatal Surgery, 2025)
Background: Body meridians, also known as energy pathways, are a foundational concept in traditional Chinese medicine (TCM) Purpose of the study: The purpose of this study was to evaluate the relationship between some selected body meridians and mechanical neck pain patients. Materials and Methods: There were 60 volunteers with mechanical neck pain of both genders. Their ages ranged from 20 to 40. They were divided into four equal four groups received treatment on meridians. The pressure algometer measures the level of discomfort. Results: pain intensity decreased significantly after treatment compared to before treatment within groups, according to a 3×2 Mixed design MANOVA (P=0.0001; P<0.05). Following treatment, the combined phonophoresis and laser group with traditional physical therapy program experienced a significant decrease in pain intensity compared to the phonophoresis and laser groups alone. This was also the case for pain intensity in classical acupoint groups. Conclusion: According to the study's findings, there was a reduction in pain intensity; however, the phonophoresis and LLLT group showed more improvement than the other groups. For reducing pain intensity, LLLT, phonophoresis and traditional physical therapy program work better together than any treatment alone.